2013
DOI: 10.1103/physrevb.88.224515
|View full text |Cite
|
Sign up to set email alerts
|

Low superfluid density and possible multigap superconductivity in theBiS2-based layered superconductorBi4O4S3

Abstract: The magnetic penetration depth λ as a function of temperature in Bi4O4S3 was studied by muon-spin-spectroscopy measurements. The superfluid density of Bi4O4S3 is found to be very low. The dependence of λ −2 on temperature possibly suggests the existence of two s-wave type energy gaps with the zero-temperature values of 0.93(3) and 0.09(4) meV. The upturn in the temperature dependence of the upper critical field close to Tc further supports multi-gap superconductivity in Bi4O4S3. The presence of two superconduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 40 publications
5
31
1
1
Order By: Relevance
“…λ(T ) is an important parameter that is used to distinguish between different possible superconducting energy gap structures and to help identify the superconducting pairing mechanism. 840 λ(T ) was measured in Bi 4 O 4 S 3 by µSR measurements [30] and using tunnel-diode-oscillator technique [32]. The superfluid density ρ, determined from these measurements, was found to be very low.…”
Section: Magnetic Penetration Depthmentioning
confidence: 99%
See 1 more Smart Citation
“…λ(T ) is an important parameter that is used to distinguish between different possible superconducting energy gap structures and to help identify the superconducting pairing mechanism. 840 λ(T ) was measured in Bi 4 O 4 S 3 by µSR measurements [30] and using tunnel-diode-oscillator technique [32]. The superfluid density ρ, determined from these measurements, was found to be very low.…”
Section: Magnetic Penetration Depthmentioning
confidence: 99%
“…Is the pairing mech- 75 anism similar to that in unconventional superconductors (i.e., Fe-based superconductors, cuprates, etc.) or is pairing more [1,30,15,31,32,33,34, 35] LaO 0.5 F 0.5 BiS 2 2.8 [6,36,8,37,15,38,39,40,41, 42] CeO 0.5 F 0.5 BiS 2 3.0 [8,43,44,27, 45] PrO 0.5 F 0.5 BiS 2 3.5 [8,46,27, 47] NdO 0.5 F 0.5 BiS 2 4.0 [10,8,26,48,49,27, 22] YbO 0.5 F 0.5 BiS 2 5.4 [ [52] likely to be phonon mediated? Herein, we provide a selective review of the large and growing body of literature concerning BiS 2 -based superconductors and related materials.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 On the other hand, the strong FS nesting was also proposed to enhance the electron-phonon interaction and make the BiS 2 -based superconductors conventional s-wave superconductors. 9,12,13 On the experimental side, the measured magnetic penetration depth as a function of temperature can be fitted by assuming a fully gapped conventional s-wave pairing symmetry, [14][15][16] thus supporting the electron-phonon interaction as the pairing glue in BiS 2 -based superconductors. However, later neutron scattering experiments suggested that the electron-phonon coupling in LaO 0.5 F 0.5 BiS 2 could be much weaker than previously expected.…”
Section: -6mentioning
confidence: 91%
“…Unlike the compounds with a lanthanide oxide spacer layer, some of which display magnetic ordering, Bi-O-S compounds have been shown not to exhibit any magnetic ordering [37], nor any magnetic anomaly in the superconducting state [38].…”
Section: Experimental Reviewmentioning
confidence: 99%
“…The TDO data is well described using a single gap s-wave model, whereas the µSR data point more towards a two-gap s-wave symmetry [38,46].…”
Section: Experimental Reviewmentioning
confidence: 99%